Protracted hyperthermia and delayed rhabdomyolysis in ecstasy toxicity: A case report. Issue 41 (9th October 2020) - Ghaffari-Rafi, Arash; Eum, Ki Suk; Villanueva, Jesus; Jahanmir, Jay
Abstract: Rationale: Despite toxicity and unpredictable adverse effects, ecstasy use has increased in the United States. Onset of hyperpyrexia, rhabdomyolysis, disseminated intravascular coagulation (DIC), among other symptoms, occurs within hours of ingestion. Moreover, patients who experience hyperpyrexia, altered mental status, DIC, and multiorgan failure, rarely survive. This case presents a chronic ecstasy user whose symptoms would have predicted mortality. The report demonstrates a patient who experiences protracted hyperthermia, with delayed rhabdomyolysis and DIC. In addition, his peak creatine kinase (CK) of 409, 440 U/L was far greater than the expected 30, 000 to 100, 000 U/L, being the second largest CK recorded in a survivor. Patient concerns: This case report presents a 20-year-old man who presented to the emergency department after experiencing a severe reaction to ecstasy. He was a chronic user who took his baseline dosage while performing at a music event. He experienced hyperpyrexia immediately (106.5°F) while becoming stiff and unresponsive. Before emergency medical service arrival, his friends placed cold compresses on the patient and rested him in an ice filled bathtub. Diagnoses: Per history from patient's friends and toxicology results, the patient was diagnosed with ecstasy overdose, which evolved to include protracted hyperthermia and delayed rhabdomyolysis. Interventions: Due to a Glasgow coma scale score of 5, he was intubated and sedated with a propofol maintenance. Hyperpyrexia resolved (temperature dropped to 99.1°F) after start of propofol maintenance. He was extubated after 24 hours, upon which he experienced hyperthermia (101.4°F at 48 hours), delayed rhabdomyolysis, and DIC (onset at 37 hours). He remained in hyperthermia for 120 hours until carvedilol permanently returned his temperature to baseline. His plasma CK reached a peak of 409, 440 U/L at 35 hours. Outcomes: After primary management with intravenous fluids, the patient returned to baseline health without any consequences and was discharged after 8 days. A follow-up of 3 months postdischarge revealed no complications or disability. Lessons: Clinically, the case highlights how physicians should be aware of the unusual time course adverse effects of ecstasy can have. Lastly, as intensity and duration of hyperpyrexia are predictors of mortality, our case indicates maintenance of sedation with propofol and use of oral carvedilol; both are efficacious for temperature reduction in ecstasy toxicity.